E-Journals Usage Trend in IUB Library (Bangladesh Journal of Library and Information Science, 2012)
This article aims to give a general understanding about the popularity of electronic resources in Independent University, Bangladesh, which would help in shaping higher education in the country. Resources usages were determined on the basis of electronic resources providers data. The article comes up with some important findings. Use of Emerald database in IUB found to be more rational compared to other three IP based databases. The ratios between the top-most and the 25th documents those opened, from Emerald 5:1, from JSTOR 13:1, from ABI/Inform 19:1, from OUP Journals 31:1. Users preferred PDF documents and Period had no influence over usage. The study only covered IP based electronic resources; password based or other free electronic resources were out of the study. This is the first case study on the use of electronic resources in Bangladesh, which would give Bangladeshi libraries a guidance regarding electronic resources subscription. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.79-91DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12924